UMP Item Trading Application - Loh, Hin Ye (2023)
A mobile application is a programme that runs on a mobile device, such as a smartphone or tablet. Despite the fact that applications are often small software units with limited capabilities, they can still deliver great service and experience to users. Mobile shopping allows users to purchase items from mobile devices by using an application like Shopee, Lazada, and so on. It’s made the process of purchasing or selling products be simplified. With reducing the waste of resources, inside UMP there have a lot of people has many used books or some used items that are transferable and want to sell to juniors to reduce the waste of resources, and juniors also can save money based on just using the used items and no need to purchase new items. All the sellers are only can advertise their items or products on social media or study group chat like telegram channel, WhatsApp group, and so on for now. Advertisement on social media or the study group chat will disturb and reduce students’ learning experience. The objective of this project is to study the existing mobile application related to mobile commerce and design and develop an application as a platform for ump students to purchase and sell items using Android Studio. It also to evaluate the functionality of the developed mobile applications that are able students to trade items. The user scope of this study is for the undergraduate UMP students and in Pekan area. Besides, the system scope is to cover transactions between seller and buyer. For the development scope, the study is contains multimedia elements such as graphics and text and using the Android Studio to develop the application. The signification of the project is students can have a platform to make transactions of items with other students. It also can give an opportunity to the students who need to start a business on this platform and for the buyers, it also can be more convenient and have a cheaper price on the items. For UMP, it can have a new platform that can help UMP students to improve their daily life and improve their experience in UMP.